Artificial molecular and nanostructures for advanced nanomachinery. Issue 33 (27th February 2018) - Ellis, Elizabeth; Moorthy, Suresh; Chio, Weng-I Katherine; Lee, Tung-Chun
Abstract : This Feature Article overviews major types of nanoscale machines to reveal common structural features and design rules across different length scales and material systems. Abstract : Artificial nanomachines can be broadly defined as manmade molecular and nanosystems that are capable of performing useful tasks, very often, by means of doing mechanical work at the nanoscale. Recent advances in nanoscience allow these tiny machines to be designed and made with unprecedented sophistication and complexity, showing promise in novel applications, including molecular assemblers, self-propelling nanocarriers and in vivo molecular computation. This Feature Article overviews and compares major types of nanoscale machines, including molecular machines, self-assembled nanomachines and hybrid inorganic nanomachines, to reveal common structural features and operating principles across different length scales and material systems. We will focus on systems with feature size between 1 and 100 nm, where classical laws of physics meet those of quantum mechanics, giving rise to a spectrum of exotic physiochemical properties. Concepts of nanomachines will be illustrated by selected seminal work along with state-of-the-art progress, including our own contribution, across the fields. The Article will conclude with a brief outlook of this exciting research area.